Green Washing and Brand Crises: Modelling Consumer Trust Repair - Rashid, Hamza; Ahmad, Wisal; Hafizullah (Pakistan Journal of Humanities and Social Sciences, 2023)
This study proposes an innovative approach to rebuilding consumer trust following the negative impact of greenwashing, which often leads to a conflicted relationship between corporations and consumers. Through a novel integration of previously unconnected concepts, such as trustworthiness dimensions (Integrity, benevolence, and competence), credibility, empathy, forgiveness, consumer trust repair, revived brand equity, and repurchase intention, this study offers a nuanced and enhanced understanding of the consumer trust repair process. The current research seeks to integrate disparate concepts and theories into a cohesive whole, resulting in a modified version of the consumer trust repair process. Prior studies have examined the phenomenon of consumer trust repair in a relatively narrow and parochial manner and have failed to provide a holistic process-based model. This study, however, attempts to provide a comprehensive, process-based model of consumer trust repair. Through this holistic approach, this research makes a valuable and meaningful contribution to the field of consumer trust repair, providing brand managers with a deeper understanding of the consumer trust recovery process, which has been largely ignored in previous studies. This unique and comprehensive approach will surely capture readers' attention, as it offers a fresh perspective on a crucial issue facing the business world today.